THE REGIONAL FEATURES OF THE SOMATOMETRIC CHARACTERISTICS IN URBAN SCHOOLGIRLS IN THE REPUBLIC OF KHAKASSIA - Гладкая, Валентина Сергеевна; Королёва, Виталия Александровна; Грицинская, Вера Людвиговна (Mother and Baby in Kuzbass, 2018)
Purpose of the study – to assess the indicators of physical development of urban schoolgirls living in the Republic of Khakassia. The material and methods. In the study participated 1623 schoolgirls aged 11 to 18 years living in the industrial center of Khakassia – Chernogorsk. The survey included a dynamic assessment of somatometric indicators (length and weight, circumference of the chest, waist and buttocks, transverse diameters of the shoulders and pelvis) and the description of the level and harmony of physical development according to WHO guidelines. The results. The increase in somatometric indicators in the examined schoolgirls occurs in accordance with the general biological pattern. The pubertal growth acceleration is observed at the age of 11 to 14 years; the maximum annual increase in length and body weight, circumferences of the chest and buttocks, the diameters of the shoulders and pelvis are recorded in the 13th year of life. During the pubertal jump of growth among the schoolgirls surveyed, the number of girls with harmonious physical development is lower; and at the beginning of the period, there are more girls with a deficit in body weight, and later with obesity. The conclusion. The revealed increase in the number of girls with disharmonious options during puberty requires the improvement of medical counseling and dispensary observation in this age group.